Antioxidative enzymes as markers for the selection of advanced sweet potato breeding lines under in vitro osmotic stress conditions - Mishra, Ananya; Tripathy, Pradyumna; Krishnappa, Hanume Gowda; Dasgupta, Madhumita; Mohanty, Sansuta; Singh, Satyapriya; Chauhan, Vijay Bahadur Singh; Arutselvan, Rameshkumar; Sahoo, Bibhuti Bhusan; Sahoo, Manas Ranjan (Frontiers in Plant Science, 2026)
Five advanced breeding lines of sweet potato were assessed for polyethylene glycol (PEG)-6000-mediated osmotic stress tolerance in vitro. Significant variation among the morphophysiological properties and antioxidative enzyme activities was observed under different levels of PEG (0, 0.1, and 0.2 MPa) incorporated in Murashige and Skoog (MS) medium. An induction of antioxidative enzymes—superoxide dismutase (SOD, Enzyme Commission [EC] 1.15.1.1), catalase (CAT, EC 1.11.1.6), ascorbate peroxidase (APX, EC 1.11.1.1), guaiacol peroxidase (GPX, EC 1.11.1.7), monodehydroascorbate reductase (MDHAR, EC 1.6.5.4), dehydroascorbate reductase (DHAR, EC 1.8.5.1), glutathione reductase (GR, EC 1.6.4.2), and polyphenol oxidase (PPO, EC 1.14.18.1)—was observed under stress compared to the control, and this induction was pronounced in the tolerant genotypes than in the susceptible ones. Among the antioxidant enzymes, CAT showed a strong positive correlation with GPX (Pearson’s correlation coefficient [r] = 0.73), whereas MDHAR was strongly and positively correlated with APX (r = 0.73) and PPO (r = 0.68). A significant increase in antioxidative enzyme activities was associated with lower growth retardation, as evident from the correlation study. Genotypes SP–30, followed by SP–18, possessed high principal component (PC1) scores and were rich in antioxidative enzymes, whereas genotypes SP–24, SP–26, and SP–28 exhibited lower enzyme activities and skewed morphological traits. The overall pattern of osmotic stress tolerance among the tested advanced sweet potato breeding lines followed the order: SP–30 > SP–18 > SP–26 > SP–24 > SP–28. The outcome of the study encourages the advancement of SP–30 for inclusion in future breeding strategies and/or its release following the official variety release procedures.